Laparoscopic management of an endometrioma complicated by an ovarian abscess - Shah, Rameshvari C.; Shah, Jitesh M.; Mehta, Meghana N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
An ovarian abscess is defined as a primary infection of the ovary without the involvement of the fallopian tube. The possible factors for the cause of ovarian abscess are: disruption of the ovarian capsule, giving access to bacteria, haematogenous and lymphatic spread. A woman with a ruptured ovarian abscess presents with features of diffuse peritonitis. An unruptured abscess is more difficult to diagnose. Unruptured abscess can be dealt with either laparotomy or laparoscopy. Ruptured ovarian abscess requires an aggressive and primarily surgical approach.